1991
DOI: 10.1111/j.1476-5381.1991.tb12529.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vasoactive substances released by platelet‐activating factor in the rat perfused heart

Abstract: 1 The coronary vascular effects of platelet-activating factor (PAF) have been intensively studied and it has been proposed that they are mediated by the release of vasoactive substances. In this study, a cascade perfusion model using two rat perfused hearts was developed to investigate the properties of PAF-released vasoactive substances and the interplay of these substances. The properties of the vasoactive substances after an injection of PAF (100pmol) in the rat perfused heart were examined by collecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The effects induced by PAF in the isolated rat heart are similar to that observed in guinea pig heart (e.g., reduction in coronary flow and developed pressure, increase in diastolic pressure and conduction arrhythmias) (188,189,334,339,340). In this animal, however, it has been shown that the PAF-induced coronary vasoconstriction is mediated by the peptide leukotrienes (leukotriene C 4 and leukotriene D 4 ) (188,189,334). This finding indicates that in the rat heart PAF may have a small direct negative effect, whereas the reduction of coronary flow consequent to production and release of endogenous leukotrienes appears to induce a major depression of cardiac contractile force.…”
Section: Myocardial Functionsupporting
confidence: 65%
“…The effects induced by PAF in the isolated rat heart are similar to that observed in guinea pig heart (e.g., reduction in coronary flow and developed pressure, increase in diastolic pressure and conduction arrhythmias) (188,189,334,339,340). In this animal, however, it has been shown that the PAF-induced coronary vasoconstriction is mediated by the peptide leukotrienes (leukotriene C 4 and leukotriene D 4 ) (188,189,334). This finding indicates that in the rat heart PAF may have a small direct negative effect, whereas the reduction of coronary flow consequent to production and release of endogenous leukotrienes appears to induce a major depression of cardiac contractile force.…”
Section: Myocardial Functionsupporting
confidence: 65%
“…In fact, the vascular effects of PAF have been shown to be largely mediated by the release of other vasoactive substances such as prostaglandins PAF 0.25 jg kg-1 i.v. ( Heffner et al, 1983;Piper & Stewart, 1986;Hu & Man, 1991), leukotrienes (Voelkel et al, 1982;Sybertz et al, 1985;Piper & Stewart, 1986) and PAF itself (Tessner et al, 1989). In addition, several lines of evidence indicate that production of endothelium-derived relaxing factor (EDRF), which is thought to be nitric oxide (NO; Palmer et al, 1987), may contribute to the vasodilator actions of PAF in in vitro preparations (Kamitani et al, 1984;Kamata et al, 1989;Chiba et al, 1990;Moritoki et al, 1992;Juncos et al, 1993).…”
mentioning
confidence: 99%
“…Another possible mediator of the constrictor effect is PAF, which is produced by PMN and can cause coronary vasoconstriction (11). PAF is reported to cause responses via the synthesis of leukotrienes and prostaglandins (12,35), and, although we were not successful in blocking responses to leukotrienes, indomethacin had no effect on the response, suggesting that PAFinduced prostaglandin production in situ is not a contributing factor in our study. PAF has been reported to cause dilator and constrictor effects that are species dependent (11).…”
Section: Discussionmentioning
confidence: 52%